There's a pest in the garden! ebook - Thomas, Jan (The Giggle Gang., 2020)
Someone's eating all the veggies in this colorful picture book with " a satisfying, funny conclusion" ( Kirkus Reviews ). There's a pest in the garden and he's eating all the vegetables! But Duck has a plan to save the day (well, sort of)... Featuring Jan Thomas's wonderfully wacky humor, rowdy repetitions, and hilarious characters, this book is sure to have young readers laughing out loud!